The role of separation of powers in ensuring public accountability in South Africa: policy versus practice - Munzhedzi, P. H. (International Conference on Public Administration and Development Alternatives (IPADA), 2017)
The Constitution of the Republic of South Africa of 1996 (1996 Constitution) makes a provision that there shall be separation of powers between the legislature, executive and judiciary, with appropriate checks and balances to ensure accountability, responsiveness and openness. This constitutional provision is adopted from a century old principle of trias politica which stipulates that power of the state must be divided amongst the three existing arms. This policy position makes a sound pronouncement that each arm of the state must be held accountable in the performance of their public functions. However, more focus of this paper is on the legislative arm in that it is the one responsible for ensuring that the executive arm accounts for all functions vested upon it by the 1996 Constitution. This conceptual paper seeks to explore the nature of the relationship between these three arms of the state, and identify challenges confronting the legislature in holding the executive to account so as to propose possible solutions to the challenges. It is recommended the legislative arm must be beefed-up to ensure that the executive arm is held accountable at all times so as to curtail maladministration, corruption and the abuse of state resources.
Journal article, Published in International Conference on Public Administration and Development Alternatives (IPADA), The 2nd Annual Conference on ‛‛ The Independence of African States in the Age of Globalisation”, July 26-28, 2017
Keywords: Separation of powers; Public accountability; Oversight; Parliament; Separation of powers -- South Africa; Government accountability; South Africa -- Politics and government